Verbal–visual harmony or dissonance? A news values analysis of multimodal news texts on climate change. (December 2017) - Dahl, Trine; Fløttum, Kjersti
Highlights: Most of the texts from both newspapers display verbal-visual harmony. Negativity and Impact are important news values in both modes. Positivity is constructed in more than a third of the Daily Mail headlines. Image selection represents a challenge in news stories on climate change. Decontextualised images and images of past disasters are used to portray the future. Abstract: The focus of this paper is on the little researched interplay between verbal and visual representations of climate change news. We apply the framework of discursive news values analysis (Bednarek and Caple, 2017 ) to investigate how climate stories are made newsworthy through language (headlines) and image (pictures). We analyse 22 texts from the broadsheet The Guardian and 28 from the tabloid Daily Mail relating to the IPCC's 5th Assessment Report and find that, broadly speaking, the same news values are constructed in both newspapers, notably the 'traditional' values of Negativity and Impact, often in combination with Eliteness and Superlativeness. There was generally a harmonious relationship between the verbal and the visual message, with language and image reinforcing or complementing each other. However, in some instances, and notably in the Daily Mail, there was a clash between the two meaning-making modes, e.g., involving Negativity constructed through language and Positivity through image. The paper also finds that selection of visuals to accompany news stories on climate change represents a newsroom challenge, e.g., when images originally produced as visual verification of a past event are used as illustrations of what the future may bring.